Students’ satisfaction with the university cafeteria: structural relationships of food quality, staff, price fairness, and ambiance / Mui Ling Dyana Chang, Norazah Mohd Suki and Norbayah Mohd Suki - Chang, Mui Ling Dyana; Mohd Suki, Norazah; Mohd Suki, Norbayah (Division of Research and Industry Linkages , UiTM Melaka, 2014)
This study aims to investigate the relationship between the food quality, price fairness, staff, and ambiance of the university cafeteria with students’ satisfaction. To test the conceptual model and test the proposed hypotheses, a quantitative survey was performed via a structured self-administered questionnaire among 78 undergraduates from Universiti Teknologi MARA (UiTM), Sabah campus, Malaysia, utilizing convenience-sampling method. Data was analyzed using Structural Equation Modeling (SEM) technique via AMOS 21.0 computer program with maximum likelihood estimation. The empirical results provided strong support that students’ satisfaction with the university cafeteria is very much influenced by food quality, followed by staff and ambiance, respectively. Implications of the study from managerial and theoretical perspectives together with directions for future research are also discussed. The findings of this study may help the university cafeteria to improve service quality and raise students’ satisfaction.